Pengaruh Motivasi Kerja Terhadap Produktivitas Karyawan PT Aldaco Citra Jaya Gresik - Avita Dwi Juliati; Anis Fitriyasari (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
Thesis with the title "The Influence of Work Motivation on Work Productivity of Production Section Employees Case Study at PT. Aldaco Citra Jaya" was written by Avita Dwi Juliati, NIM 20113005, Faculty of Management, STIE IBMT, management study program, which was supervised by Mrs. Is Fadhillah, S.E,. M.Si. This study aims to examine the significant effect of motivation on employee productivity at PT Aldaco Citra Jaya, either partially or simultaneously. The research uses a quantitative and descriptive approach. Sources of data used in this study are primary and secondary data obtained from distributing questionnaires to all employees of PT. ALdaco Citra Jaya. This study uses the method of descriptive analysis, simple linear analysis, partial hypothesis testing (t test), and the coefficient of determination (R2). The results of this study indicate that there is a significant and positive relationship between motivation and work productivity of production employees at PT. Aldaco Citra Jaya by 75%.